PUBLIC INTEREST AS AN ‘EMPTY SIGNIFIER’: DISCOURSE HEGEMONY STRATEGY OF PRO-DAM GROUP IN THE CONTESTATION OF THE DEVELOPMENT DISCOURSE OF THE BENER DAM NATIONAL STRAGIC PROJECT - Achyansyah, Muhammad Nadhif; Djuyandi, Yusa (JWP (Jurnal Wacana Politik), 2026)
This article examines how the discourse of public interest is constructed and mobilized by pro-dam actors to legitimize the construction of the Bener Dam National Strategic Project amid resistance against andesite quarry mining in Wadas Village, Purworejo Regency. Using Ernesto Laclau and Chantal Mouffe’s discourse analysis framework, this study employs qualitative methods to analyze textual and non-textual data drawn from official government documents, policy statements, press conferences, mass media coverage, and public communications by central and local governments as well as pro-dam community actors. The analysis shows that public interest functions as an empty signifier that is articulated as a nodal point to unify diverse urgencies—economic growth, water resource management, food security, energy, and tourism—into a single hegemonic demand for the continuation of the Bener Dam project. Through repeated articulation, pro-dam actors succeed in stabilizing the meaning of the project as a collective good while simultaneously fragmenting and delegitimizing the chain of equivalence formed by opposing discourses related to environmental damage, eco-spirituality, livelihoods, and human rights. The article concludes that the hegemonic deployment of public interest enables pro-dam groups to dominate the discursive field of development, although this fixation remains contingent and open to counter-hegemonic re-articulation.